Plant form the basis of forage land grass study area (Eurasian Journal of Ecology, 2016)
This article describes the results of research geobotanic natural grasslands Usharalsk rural district. A list of plants are found in the studied area and the types of stocks kormavyh plants. By raznobraziyu vegetation were identified 119 species of trees belonging to 27 families.
Keywords: pastures; hayfields; study area; life forms